Sequential Use of Sarilumab and Baricitinib in Severe COVID-19 Pneumonia: A Case Report - Roberta, Gagliardini; Alessandra, Sacchi; Paolo, Campioni; Stefania, Cicalini; Germana, Grassi; Sandrine, Ottou; Castilletti, Concetta; Chiara, Agrati; Andrea, Antinori (Archives of Clinical and Medical Case Reports, 2020)
Background: Severe COVID-19 associated pneumonia patients may exhibit features of systemic hyper-inflammation. Both anti-IL-6 and anti-JAK drugs are curently under investigation for the hyperinflammatory syndrome of COVID-19 disease. Here we report a clinical case with a complete panel of cytokine levels and immunological profiling of T cell, plasmacytoid and myeloid dendritic cells. Case Presentation: An adult patient with severe COVID-19 pneumonia and documented hyper-inflammation has been treated with antivirals and off-label sarilumab intravenously, with poor response. Subsequently, he was treated with off-label oral baricitinib for 14 days, with clinical, radiological and laboratoristic response, measured also with IL1b, IL-6, IL-8 and TNF-a levels. Conclusions: Baricitinib was well tolerated and was able to reduce the inflammatory mediators, confirming its role in diminishing the excessive inflammatory response. This case is the first presented with an extensive characterization and shows a possible use of baricitinib as rescue therapy, after anti-IL6 treatment, for COVID-19.